(NsTATXI(B; s (NpISXMA (B/ s (N~ASTX (B2s - (NgRIGORXEW(B, (NaPOLLONs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1990)
(Nw TOM WHODQT KRITI^ESKIE STATXI aP(B. (NgRIGORXEWA (B("(NwZGLQD NA RUSSKU@ LITERATURU SO SMERTI pU[KINA(B", "(NpOSLE (B"(NgROZY(B" (NoSTROWSKOGO(B", "(NgRAF l(B. (NtOLSTOJ I EGO SO^INENIQ(B" (NI DR(B.), (NA TAKVE EGO PISXMA m(B. (Np(B, (NpOGODINU(B, (Ne(B. (Ns(B. (NpROTOPOPOWOJ I n(B. (Nn(B. (NsTRAHOWU(B.s
rus
Keywords: (NsTATXI I ZAMETKIs; (NpISXMAs